The relational expectations of women managing women. Issue 1 (6th March 2017) - Hurst, Jane; Leberman, Sarah; Edwards, Margot
Abstract : Purpose: The purpose of this paper is to examine the expectations women have of their women managers and/or women employees and to suggest personal and organizational strategies to strengthen those relationships. Design/methodology/approach: Building on a first phase of research using narrative inquiry into the lived experiences of women managing and/or being managed by women, workshops were held with 13 participants to explore their relationship expectations of women managers and/or employees. Findings: While the participants initially believed they expected the same things of a manager or employee irrespective of gender, a closer examination revealed gender-based expectations. Women expect a higher degree of emotional understanding and support from a woman manager, than they would from a man. They also expect a woman manager to see them as an equal, take a holistic view of them as people, understand the complexities of their lives and provide flexibility to accommodate those complexities. Research limitations/implications: This is an exploratory study in an under-researched area. Extensive further research is warranted. Practical implications: Understanding the expectations women have of their women managers enables the development of both personal and organizational strategies aimed at strengthening those relationships. Originality/value: These findings begin a dialogue on the often-unspoken and unrecognized gender-based expectations women have of their relationships with women managers and/or women employees. Although considerable research exists on gender stereotypes in the workplace, little research exists on these gender-based relational expectations.